Role of Epidural Steroid Injection in Pain Reduction and Functional Recovery in Prolapsed Lumbar Intervertebral Disc (PLID) (The Insight, 2025)
Introduction: Prolapsed lumbar intervertebral disc (PLID) is a leading cause of low back pain and radiculopathy, significantly influencing patients' quality of life. ESIs reduce inflammation and nerve root irritation, offering short-term pain relief and improved mobility. Methods & Materials: This one-year retrospective study (January 2022–December 2023) at Gazi and Khulna Medical Colleges, Bangladesh, included 50 adults (20–60 years) with MRI-confirmed lumbar disc prolapse unresponsive to ≥4 weeks of conservative therapy. Patients received interlaminar or transforaminal epidural steroid injections. Pain (VAS), disability (ODI), complications, and satisfaction were evaluated at baseline, 1 week, 1 month, and 3 months. Result: The study included 50 patients with a mean age of 41.6 years; 56% were male, and 60% had sedentary occupations. The most common disc prolapse level was L4-L5 (56%), and protrusion was the predominant type (44%). Interlaminar ESI was most frequently used (60%) with methylprednisolone (64%), and 60% received a single injection. Significant reductions in pain and disability were observed, with VAS scores dropping from 7.6 to 2.8 and ODI scores from 58.2% to 24.3% at 3 months (p
Keywords: Epidural Steroid Injection (EPI); Pain Reduction; Functional Recovery; Prolapsed Lumbar Intervertebral Disc (PLID)